Hubungan Antara Tingkat Pendidikan, Usia Kehamilan, dan Paritas dengan Kejadian Anemia pada Ibu Hamil di PUSKESMAS Gunung Sari Lombok Barat Tahun 2023 - Jannah, Dina Raodatul; Mahayani, Ida Ayu Made; Herlinawati, Herlinawati; Lestari, Novianti Anggie (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the relationship between education level, gestational age and parity with the incidence of anemia in pregnant women at Gunung Sari Health Center, West Lombok in 2023. This study is an analytic observational using case-control design. The sampling technique was purposive sampling. The study sample was 256 samples with each case and control sample according to the inclusion and exclusion criteria. The data obtained were analyzed with the chi-square correlation test. The results of this study Showed (1) Low education level respondents as many as 50 respondents (19.5%) and high education level as many as 206 (80.5%). (2) Respondents with risky gestational age were 147 respondents (57.4%) and non-risky parity were 109 respondents (42.6%). (3) Respondents with risky parity were 99 (38.7%) and non-risky parity were 157 (61.3%). (4) There is a relationship between low education level and the incidence of anemia in pregnant women with a p-value of 0.040 and OR 2.037. (5) There is a relationship between risky gestational age and the incidence of anemia in pregnant women with a p-value of 0.000 and OR 9, 348. (6) There is no association of parity risk with the incidence of anemia in pregnant women with a p-value of 1,000. (7) There is a significant relationship between education level and gestational age with the incidence of anemia in pregnant women. (8) There is no significant relationship between parity and the incidence of anemia in pregnant women at Puskesmas Gunungsari West Lombok in 2023.